Análisis del comportamiento de tensiones máximas inducidas en pavimentos rígidos debido al reemplazo parcial de losas (2020)
The objective of this study is to analyze the behavior of the maximum stresses induced in concrete slabs as a result of modifications in their geometry. This condition is due to maintenance operations that consider the partial replacement of paving slabs. The analysis is carried out by modeling finite elements of the pavement in sections that consider 2 transversal slabs and 3 longitudinal slabs. A square geometry, traditionally used in Chile, of 3,500 mm (length) x 3,500 mm (width) has been used as the base for each slab. The effect of partial replacement of the central slab by variable lengths in combination with variations in slab thickness of 150 mm, 160 mm, 180 mm and 200 mm has been studied for 3 types of subgrade. The models have been solved by means of finite element analysis and for this the EverFE 2.26 software has been used, which has been widely used for the study of rigid pavements. The maximum stresses induced by the most critical position of the load have been studied, which corresponds to the positioning of the single axle with dual tires on the edge of the slab. The results allow recommending a limit configuration in the partial replacement of slabs in order to control the maximum stresses induced and thereby avoid the reduction of their useful life. The determined increase in the stresses in the slab is between 3.63 and 7.61% and these values allow calculating by fatigue models, a decrease in the total number of load applications of 27% for slab thicknesses of 150mm (K=0.064 MPa/mm) and 14% for slabs of 200mm (K=0.064 MPa/mm) thickness, which is reflected in a reduction in its useful life.